Advancements in aluminum matrix composites reinforced with carbides and graphene: a comprehensive review - Alam, Mohammad Azad; Ya, Hamdan B.; Azeem, Mohammad; Mustapha, Mazli; Yusuf, Mohammad; Masood, Faisal; Marode, Roshan Vijay; Sapuan, Salit Mohd; Ansari, Akhter Husain (Walter De Gruyter GmbH, 2023)
Automotive and aircraft industries are advancing swiftly, creating a constant need for innovative and trustworthy materials. Aluminum composites (aluminum matrix composites AMCs) exhibit enhanced mechanical and tribological behaviors when contrasted to their conventional equivalents and as a result have superior potential to be widely accepted for automotive and aircraft engineering and other component applications. This study aims to provide a thorough and critical analysis of the most recent research initiatives concerning the processing, characteristics, and applications of AMCs. It covers the recent advancements in the aluminum-based composites reinforced with SiC, TiC, and graphene, fabrication methods, and mechanical properties of AMCs. Graphene nanoplatelets are many times stronger and yet lighter than steel and other metals, and thus a good contender for reinforcing them. However, the homogeneous distribution of graphene into the metal or aluminum is a challenging aspect for material researchers. The fabrication techniques for AMCs for achieving homogeneous distribution of graphene are critically reviewed. The mechanical properties, specifically microhardness, wear behavior, and tensile strength of aluminum-based composites, are reviewed and analyzed. Finally, a way forward for fostering further development in this area has been discussed.